PENGARUH METODE GUIDED DISCOVERY TERHADAP HASIL BELAJAR IPA SDN 33 KECAMATAN PONTIANAK BARAT - Prasetyo, Melza Dary (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to analyze the influence and how much of guided discovery method affected the student learning outcomes in science learning on the fourth grade elementary school 33 western Pontianak district. This research used an experimental method with quasi eksperimental form using Nonequivalent Control Group Design. The sample in this research were all fourth grade elementary school 33 western Pontianak district which consists of 63 people.The results of analysis using t-test was > 1,6708. It means that there was a significance influence by using guided discovery method affected the student learning outcomes in science learning on the fourth grade elementary school 33 western Pontianak district. Based on the effect size (ES) result, it obtained 0,53. It means that learning by using guided discovery method give a moderat effect to student learning outcomes in science learning on the fourth grade elementary school 33 western Pontianak district. Keywords: guided discovery method, learning outcomes, science learning